(untitled) (Humanis, 2026)
The discourse of Yamato damashii ’Japanese Spirit’ or ‘Japanese Soul’ constructs the knowledge about "Japanese people", "Japanese culture" and "nationalism." This paper discusses Saiichi Maruya’s novel entitled Sasamakura. The analysis focuses on Hamada, the major character. The analysis is carried out by using a critical paradigm, by dismantling the aspect of power that constructs the meaning of Japanese food by using Stuart Hall’s theory of identity and Michel Foucault’s work on the discursive construction of power/knowledge. This research found that, food that originally belonged to foreigners, was shed from its original identity through reintegration and reproduction to become what is called Japanese cuisine. What is known as nihon ryōri or washoku occupies a more special position because it is considered has deep roots in Japanese history, with cooking and serving techniques, authentic, and does not mix with other cultures that are considered inferior. Therefore, Japanese people who are considered to have a Japanese identity are expected to represent Yamato damashii ’Japanese Soul’ when they choose to eat nihon ryōri and eat in a predetermined manner or etiquette.